A Nationwide multicenter registry and biobank program for deep phenotyping of idiopathic and hereditary pulmonary arterial hypertension in Korea: the PAH platform for deep phenotyping in Korean subjects (PHOENIKS) cohort - Albert Youngwoo Jang; Sungseek Kim; Su Jung Park; Hanul Choi; Pyung Chun Oh; Seyeon Oh; Kyung-Hee Kim; Kye Hun Kim; Kyunghee Byun; Wook-Jin Chung; for the PHOENIKS Investigators (BMC, 2019)
Abstract Background Pulmonary arterial hypertension (PAH) is a progressive, chronic disease without curative treatment. Large registry data of these patient populations have been published, although, phenotypic variants within each subtype of PAH have not been elucidated. As interest towards personalized medicine grows, the need for a PAH cohort with a comprehensive understanding of patient phenotypes through multiomics approaches, called deep phenotyping, is on the rise. The PAH Platform for Deep Phenotyping in Korean Subjects (PHOENIKS) cohort is designed to collect clinical data as well as biological specimens for deep phenotyping in patients with idiopathic PAH (IPAH) and heritable PAH (HPAH) in Korea. Methods A total of 17 regional hospitals are currently working on enrolling up to 100 consecutive IPAH/HPAH patients for obtaining clinical data and biological specimens across Korea. The diagnosis of PAH is based on right heart catheterization. All clinical data is stored in a government-based online database. Each participating hospitals collect a whole blood sample from each patient, through which DNA, RNA, serum, plasma, and peripheral blood mononuclear cells will be extracted from the buffy coat layer for further multiomics analysis. Results Not applicable. Conclusions The PHOENIKS cohort is enrolling IPAH and HPAH patients across Korea to determine the prognosis and drug response in different phenotypic variant. The data generated by this cohort are expected to open new doors for personalized medicine in PAH patients of South Korea. Trial registration ClinicalTrials.gov NCT03933579. Registered on May 1st, 2019.